The case of Isaac Brown: fugitive slave - Prince, Bryan (Ontario History)

(untitled) (The Ontario Historical Society, 2007)
Few topics in Ontario’s rich history rival that of the Underground Railroad in terms of human drama and intrigue. One of those individual stories that graphically illustrate that point is that of Isaac Brown. His epic story unfolded through time and place from a Maryland plantation to a New Orleans auction block to a Philadelphia courthouse in the free state of Pennsylvania. The separation from his family at the end of a slave-traders whip and their later tearful reunion stretched the emotions to its extremities. But the times and the circumstances dictated that Canada West would be the only place where this family could find freedom and where this international thriller could peacefully end.